The Effects of Mindfulness on Sensory Marketing: The Role of Mental Imagery Vividness and the Sensory Type Number - Bingcan Li; Yi Jiang; Yuanzhi Wu; Lei Wang (Behavioral Sciences, 2023)
Mindfulness refers to paying attention to the present sensation, attention, and thoughts without judgment and is proven to enhance sensations. Although researchers began to investigate the role of mindfulness in consumer decision-making, few studies pay attention to the impact of mindfulness on the effect of sensory marketing. In the current study, we investigated whether and how mindfulness enhances the purchase intentions of sensory marketing products. We conducted three studies (n = 593) to test our hypotheses. The first study tested the correlation between trait mindfulness and the purchase intentions of sensory ads. The results showed that the level of trait mindfulness and purchase intentions were positively correlated. The second study primed the state mindfulness of participants and demonstrated that high-level state mindfulness enhanced purchase intentions, which was moderated by the number of sensory types. The third study further tested the mental imagery vividness and proved the mediating role of vividness between state mindfulness and purchase intentions. The current study shows the enhancing effect of mindfulness on purchase intentions. This effect is moderated by the number of sensory types and mediated by the vividness of mental images. Our study illustrates the critical contribution of mindfulness to promoting sensory marketing.